Genetic Heterogeneity of Susceptibility Gene in Different Ethnic Populations: Refining Association Study of PTPN22 for Graves’ Disease in a Chinese Han Population - Xue, Liqiong (Public Library of Science, 2013)
In our previous studies, we presumed subtypes of Graves’ disease (GD) may be caused by different major susceptibility genes or different variants of a single susceptibility gene. However, more evidence is needed to support this hypothesis. Single-nucleotide polymorphism (SNP) rs2476601 in PTPN22 is the susceptibility loci of GD in the European population. However, this polymorphism has not been found in Asian populations. Here, we investigate whether PTPN22 is the susceptibility gene for GD in Chinese population and further determine the susceptibility variant of PTPN22 in GD. We conducted an imputation analysis based on the results of our genome-wide association study (GWAS) in 1,536 GD patients and 1,516 control subjects. Imputation revealed that 255 common SNPs on a linkage disequilibrium (LD) block containing PTPN22 were associated with GD (P<0.05). Nine tagSNPs that captured the 255 common variants were selected to be further genotyped in a large cohort including 4,368 GD patients and 4,350 matched controls. There was no significant difference between the nine tagSNPs (P>0.05) in either the genotype distribution or allelic frequencies between patients and controls in the replication study. Although the combined analysis exhibited a weak association signal (P (combined) = 0.003263 for rs3811021), the false positive report probability (FPRP) analysis indicated it was most likely a false positive finding. Our study did not support an association of common SNPs in PTPN22 LD block with GD in Chinese Han population. This suggests that GD in different ethnic population is probably caused by distinct susceptibility genes.